2014
DOI: 10.1007/s00253-014-5639-1
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like particles in picornavirus vaccine development

Abstract: Virus-like particles (VLP), which are similar to natural virus particles but do not contain viral genes, have brought about significant breakthroughs in many research fields because of their unique advantages. The ordered repeating epitopes of VLP can induce immunity responses similar to those prompted by natural viral infection; thus, VLP vaccines are regarded as candidate alternatives to whole-virus vaccines. As picornavirus has serious impacts on human and animal health, the development of efficient and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Virus-like particles (VLPs) are multi-protein structures that mimic the organization and conformation of authentic native viruses but lack the viral genome [53]. They are safe and effective tolls that are widely used in studying the pathogenic mechanisms of virus infection, efficacy evaluation of drugs and vaccines, and drug delivery [54]. For example, the corresponding VLPs have been already used to determine the neutralizing antibodies induced by SARS-CoV and H5N1 vaccines [55,56].…”
Section: Means Of Efficacy Evaluationmentioning
confidence: 99%
“…Virus-like particles (VLPs) are multi-protein structures that mimic the organization and conformation of authentic native viruses but lack the viral genome [53]. They are safe and effective tolls that are widely used in studying the pathogenic mechanisms of virus infection, efficacy evaluation of drugs and vaccines, and drug delivery [54]. For example, the corresponding VLPs have been already used to determine the neutralizing antibodies induced by SARS-CoV and H5N1 vaccines [55,56].…”
Section: Means Of Efficacy Evaluationmentioning
confidence: 99%
“…47,48 VLPs is a potentially safe subunit vaccine that can induce immune responses similar to those prompted by natural viral infection. 49 VLPs present repetitive high-density displays of epitopes and exhibit excellent adjuvant properties capable of inducing strong immune responses. 50 It has been found that VLPs are more stable and considerably more immunogenic than purified protein antigens.…”
Section: Recombinant Protein Subunit Vaccinesmentioning
confidence: 99%
“…Novel vaccines based on recombinant FMDV empty capsids (Lewis et al, 1991;Abrams et al, 1995;Cao et al, 2009;Li et al, 2011;Gullberg et al, 2013;Guo et al, 2013;Porta et al, 2013aPorta et al, , 2013bDong et al, 2014) are also being investigated to avoid the risks of virus escape or deficient inactivation during vaccine production, while still preserving the full immunogenicity and antigenic spectrum of current vaccines. Such vaccines would also allow differentiation between infected and vaccinated animals (DIVA assays).…”
Section: Introductionmentioning
confidence: 99%